The factors related to risk of osteoarthritis in runners: ปัจจัยเสี่ยงต่อการเกิดข้อเสื่อมในนักวิ่ง - P, Ryden; N, Kongchouy (Biomedical Sciences and Clinical Medicine, 2020)
Whether or not running leads to the development of knee or hip osteoarthritis has been a much-debated topic and is often a question that most people would like to know. Many studies reported the effect of running on risk for osteoarthritis, but some of them have reported with conflicting results. However, many studies had shown the factors may be increased risk of the osteoarthritis progression in runners. Recent report showed evidence suggesting that lower-level running may be protective against the development of osteoarthritis, whereas higher-level running may increase risk of developing osteoarthritis. This article need to describe the factors related osteoarthritis risk in runners, which is beneficial to medical personnel in providing advice to avoid the risk factors for further osteoarthr.